ROLE OF ANTIBIOTIC STEWARDSHIP PROGRAM IN IMPROVING RATIONAL THIRD-LINE ANTIBIOTIC USE IN TYPE-2 DM INPATIENTS AT FATMAWATI HOSPITAL - Rizky Farmasita Budiastuti (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2025)
Type-2 diabetes mellitus (T2DM) is the most common metabolic disorders, caused by a combination of two factors: damaged insulin secretion by pancreatic β-cell and the inability of insulin-sensitive tissues to respond appropriately to insulin. Epidemiological data reveal alarming values that predict a concerning future for T2DM. According to the International Diabetes Federation (IDF), in 2019, diabetes caused 4.2 million deaths, and 463 million adults aged between 20-79 years old were living with diabetes, a number that is projected to increase up to 700 million by 2045. Based on data from RISKESDAS in 2018, the prevalence of DM in Indonesia has increased from 6.9% in 2013 to 8.5% in 2018. The Antimicrobial Resistance Control Program (PPRA) team is essential in the development and implementation of evidence-based guidelines and policies. The purpose of this study was to determine the profile of patients receiving antibiotic therapy and the use of third-line antibiotics in T2DM patients at Fatmawati Hospital during the July-December 2021 period. This research used a retrospective descriptive design with a non-experimental approach. The sample size consisted of 52 medical records that met the inclusion criteria. The results showed that patients receiving the most antibiotic treatment were between the ages of 55-64 years (38.5%), women (52%), and those with diabetic foot complications (51.8%). The single and most used combination antibiotics were ampicillin-sulbactam (34.7%) and ampicillin-sulbactam+metronidazole (29.2%). 28.8% of the patients were recommended to receive third-line antibiotics and received considerations from the PPRA team, of which 73.33% obtained approval.